1961
DOI: 10.1107/s0365110x61000048
|View full text |Cite
|
Sign up to set email alerts
|

Hartree–Fock atomic scattering factors for the iron transition series

Abstract: Atomic scattering factors for thirty-five atoms and ions of the iron group transition series (Se through Cu) have been determined from Watson's recently calculated Hartree-Fock wave functions and compared with the few other available calculations. Principal scattering factors were also computed, following the methods of Freeman, for the 3d electrons of those atoms containing nonspherical charge distributions. As shown by Weiss & Freeman these are all that are needed for determining (from the measured neutron f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
4

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 631 publications
(103 citation statements)
references
References 8 publications
4
95
0
4
Order By: Relevance
“…The octahedral Fe 3+ results closely follow the free ion curve but the tetrahedral values show a marked contraction. In our powder experiment no information could be obtained concerning the shape of the form factor and the free ion data of Watson & Freeman (1961) have been used. A contraction of the Fe 3+ form factor would result in our value of the tetrahedral moment being too low by 2-3 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The octahedral Fe 3+ results closely follow the free ion curve but the tetrahedral values show a marked contraction. In our powder experiment no information could be obtained concerning the shape of the form factor and the free ion data of Watson & Freeman (1961) have been used. A contraction of the Fe 3+ form factor would result in our value of the tetrahedral moment being too low by 2-3 %.…”
Section: Discussionmentioning
confidence: 99%
“…The complex nature of the powder pattern excluded the possibility of refinement based on integrated intensities and instead the structural parameters were refined by least-squares analysis of the diffraction profile (Rietveld, 1967) All the data collected in the range 8°<20<95 ° were used in the refinement and the contribution to the profile from the background was estimated by hand. The free ion Fe 3÷ form factor (Watson & Freeman, 1961) and the following scattering lengths were used: bo--0-58 × 10 -12 cm; bFe=0"951 × 10 -12 cm (Neutron Diffraction Commission, 1972) and bsr--0"692 × 10 -12 cm (Cooper & Rouse, 1972). …”
Section: Neutron Diffractionmentioning
confidence: 99%
“…The total number of valence electrons was assumed to be seven, as direct integration had shown that the charge of Mn was very small. The calculation was done for the two configurations 3d54s 2 (International Tables for X-ray Crystallography, 1974) and 3d 7 (Watson & Freeman, 1961). The proportionality coefficients, obtained by fitting the theoretical and experimental curves up to 0.6/k from the Mn nucleus, were 2.0 (2) and 2.3 (2) respectively.…”
Section: Metal Configurationmentioning
confidence: 99%
“…Atomic form factors for Fe(II) were taken from Watson and Freeman [22] and scattering lengths from Bacon [23]. The agreement indices which are referred to have been given previously [4,21].…”
Section: Magnetic Structure and Interlay Er Interactionsmentioning
confidence: 99%